Kiss me deadly - Van Camp, Richard 1971- (Healthy Aboriginal Network, 2011)
A range of issues are covered--from respect and communication in relationships, to pregnancy and sexually transmitted infections, two-spirit people and sexual health as a career or youth led project.--From Publisher's website
Keywords: Nonfiction comic books, strips, etc; Comic books, strips, etc -- Canada; Indians of North America -- Comic books, strips, etc; Indigenous youth -- Canada -- Comic books, strips, etc; Sexual health -- Comic books, strips, etc; Indianer; Jugend; Sexualerziehung; Nordamerika; Comic